El Partido Peronista Femenino: la gestación política y legal - Carolina Barry (Centre de Recherches sur les Mondes Américains, 2007)
Peronism arose when political participation was limited to men. Peronism –which included the absent sectors in the political scene through the Feminine Suffrage Law and the Peronist Feminine Party (PFP)- strived to change the political situation for women. The fact that PFP ended up as an exclusive female party was a product of two circumstances. First, it was unthinkable in the early years of the Peronist Party, to include women in its political structure. Second, Eva Perón was setting aside her role as First Lady to become a strong political leader, an unimaginable situation for a woman in the middle of the 20th century. The differences between the men’s and women’s parties can be analysed through a careful study of the founding assembly of the PFP, particularly in terms of differences in methods used for the session, the use of symbols, behaviour and speech of the various groups.